Hashar: Unlocking Traditional Collective Works Practice as Integrated Cultured Islamic Philanthropy Model - Khalimovna, Khilola; Omonova, Nilufar (Institut Agama Islam Negeri Parepare, 2024)
Purpose – This study explores the role of Hashar as a traditional collective work practice in Uzbekistan and its integration with Islamic philanthropic principles.. The findings reveal that Hashar embodies the principles of mutual assistance (Takaful) and voluntary service (Sadaqah), effectively bridging cultural heritage and Islamic values. Method – Using a mixed-methods approach, data were collected through field observations, in-depth interviews with community leaders and religious scholars, and analysis of relevant historical and cultural records. Findings – The results highlight Hashar’s adaptability in addressing contemporary challenges, such as mobilizing community resources in underserved areas and fostering intergenerational engagement. Practical implications –Leveraging digital platforms to modernize Hashar coordination, forming partnerships with NGOs, and integrating Hashar with formal philanthropic mechanisms like Zakat and Waqf. Originality/value – The interplay between tradition and modern Islamic philanthropy, offering actionable strategies for policymakers and community leaders to promote culturally aligned sustainable development